The translation of relative clauses from Arabic to English and vice versa / Shehda R.S. Abuisaac - Shehda, R.S. Abuisaac (2016)

(untitled)
The purpose of this study is to investigate the extent to which students at the English department of Al-Aqsa University in Palestine translate relative clauses from Arabic to English and vice versa. The study aims to investigate which Vinay and Darbelnet’s (1995)translation proceduresare used in translating relative clauses from Arabic to English and vice versa. The study also investigates whether students’ translation is geared towards Nida’s (1969) formal or dynamicequivalence when translating relative clauses from Arabic to English and vice versa. Furthermore, the study examinesthe extent to which the students’ translation achieves effectiveness in conveying the meaning in the source language text. Finally, the study investigates whether the Accessibility Hierarchy Hypothesis (AHH)(Keenan and Comrie, 1972) can be valid andappliedto the six grammatical functions of relative pronouns when students translate relative clauses from Arabic to English and vice versa. The significance of this study is based on the fact that none of the previous studies on Arabic-English and English-Arabic translations have investigated the validity of the translation procedures, formal and dynamic equivalence, and AHH in translating relative clauses.A diagnostic test was designed in both languages for purposes of data collection and data analysis, where each test includes 18 texts divided on the six grammatical functions of relative pronouns. The data of the study are mainly analyzed qualitatively. The tests were administered to a sample of ten graduate students. The results of this study show thatthe first translation procedure used for translating relative clauses is literal translation; transposition is second;modulation is third, and equivalence is fourth. Dynamic equivalence is used more; and more effectively applied than formal equivalence in translating relative clauses from Arabic to English. On the other hand, formal equivalenceis used more, and applied more effectively than dynamic equivalence in translatingrelative clauses from iv English to Arabic. Students’ incomplete mastery of grammatical categories is one of the main reasons for their incorrect translation of relative clauses in Arabic and English. Finally, the findings indicate that Keenan and Comrie’s (1972)AHHis valid in translating relative clauses from Arabic to English.However, the hypothesis is not valid in translating relative clauses from English to Arabic. Furtherparticipants in this study found it easier to translate relative clauses to their native language.